Ijob - ein Buch der Reichen? - Oesch, Josef M. (Zeitschrift für katholische Theologie, 1999)
In the recent research the thesis was postulated that the very problem of the Book of Job – the truth of the doctrine of divine retribution – was a problem of the big landowners (E. A. Knauf) or of the members of the upper-class (D. J. A. Clines). The literary investigation of the profile of the addresses claims that their milieu is to be found in the centre of the JHWH-religion during the the second temple period. There are intertextual relations not only to the sapiential or prophetic literature but also to Pentateuch. They presuppose a profound knowledge of and probably also the observance of, these texts. Therefore another hypothesis is more likely: The Book of Job tries to give an answer to questionings of the covenant-theology (Dtn 28) during the second temple period. A materialistic hermeneutic does not oppose to this thesis. An author belonging to the upper-class and defending the interests of his class could not do so without giving a solution to a central problem of the JHWH-religion.